Inter and intra-specific crossability studies on Mangifera species - MAHANTI, KISHOR KUMAR; SRIVASTAV, MANISH; SINGH, SANJAY KUMAR; DINESH, M R (The Indian Journal of Agricultural Sciences, 2022)
Inter-specific and inter-varietal crosses were attempted using Mangifera indica cv. Amrapali as a female parent and M. odorata and M. indica cv. Vanraj as male donor parents (2016–19). Initial fruit set after 7 days of pollination (DAP) was 81.48%, which reduced to 2.48% at harvest. However, in inter-specific crosses, initial fruit set was 79.89%, which reduced to 0.45% at the time of harvesting. Progenies obtained from inter-varietal and inter-specific crosses were subjected to confirmation of parentage using SSR markers. Eight polymorphic SSR markers were used to estimate the paternity, maternity and new alleles in the hybrids. Based on fragment analysis, the paternity, maternity and new alleles of 12 inter-specific and 17 inter-varietal hybrids were estimated by finding a similar number of alleles between the offsprings and parents. Among inter-specific hybrids, AO2, AO7, AO11, and AO12 showed ≥50% of paternal allele inheritance, while AO1, AO2, AO4, AO5, AO7, AO8, AO9, AO10 and AO12 showed ≥50% of maternal allele inheritance. Inter-specific hybrids such as AO1, AO3, AO5, AO9, AO10 and AO11 inherited new alleles. Among inter-varietal hybrids, AV1, AV2, AV4, AV5, AV6, AV10, AV11, AV12, AV13, AV14, AV15 and AV17 possessed ≥50% paternal allele, while, AV1, AV2, AV3, AV5, AV6, AV7, AV8, AV10, AV11 and AV15 had ≥50% maternal allele. Three inter-varietal hybrids, viz. AV8, AV9 and AV16 inherited new alleles. It is concluded that SSRs markers are useful in ascertaining the parentage of hybrids obtained from inter-specific and inter-varietal crosses in mango.